Confinement Effects in Catalysis Using Well-Defined Materials and Cages - Mouarrawis, Valentinos; Plessius, Raoul; van der Vlugt, Jarl Ivar; Reek, Joost N. H. (Frontiers in Chemistry, 2018)
This review focuses on the effects that confinement of molecular and heterogeneous catalysts with well-defined structure has on the selectivity and activity of these systems. A general introduction about catalysis and how the working principles of enzymes can be used as a source of inspiration for the preparation of catalysts with enhanced performance is provided. Subsequently, relevant studies demonstrate the importance of second coordination sphere effects in a broad sense (in homogeneous and heterogeneous catalysis). Firstly, we discuss examples involving zeolites, MOFs and COFs as heterogeneous catalysts with well-defined structures where confinement influences catalytic performance. Then, specific cases of homogeneous catalysts where non-covalent interactions determine the selectivity and activity are treated in detail. This includes examples based on cyclodextrins, calix[n]arenes, cucurbit[n]urils, and self-assembled container molecules. Throughout the review, the impact of confined spaces is emphasized and put into context, in order to get a better understanding of the effects of confinement on catalyst performance. In addition, this analysis intends to showcase the similarities between homogeneous and heterogeneous catalysts, which may aid the development of novel strategies.